2006
DOI: 10.1111/j.1728-4457.2006.00105.x
|View full text |Cite
|
Sign up to set email alerts
|

Political History and Disparities in Safe Motherhood Between Guatemala and Honduras

Abstract: Each year, worldwide, more than 500,000 women die of complications from childbirth, making this a leading cause of death globally for adult women of reproductive age. Nearly all studies that have sought to explain the persistence of high maternal mortality levels have focused on the supply of and demand for particular health services. We argue that inquiry on health services is useful but insufficient. Robust explanations for safe motherhood outcomes require examination of factors lying deeper in the causal ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 54 publications
1
19
0
Order By: Relevance
“…First, some studies have shown variation in women's health-seeking behavior across ethnic groups. Indeed, Shiffman and Garces del Valle (2006) point out that discriminatory maltreatment of Mayans has made them suspicious of state-run institutions, including medical facilities. In Guatemala, there are two main ethnic groups: indigenous people and Ladinos.…”
Section: Choosing Child Delivery Medical Providers In Guatemalamentioning
confidence: 98%
See 1 more Smart Citation
“…First, some studies have shown variation in women's health-seeking behavior across ethnic groups. Indeed, Shiffman and Garces del Valle (2006) point out that discriminatory maltreatment of Mayans has made them suspicious of state-run institutions, including medical facilities. In Guatemala, there are two main ethnic groups: indigenous people and Ladinos.…”
Section: Choosing Child Delivery Medical Providers In Guatemalamentioning
confidence: 98%
“…Thus, the decision to see a midwife may increase the likelihood of stillbirths and deaths at childbirth. In the 1990s, Guatemala's Ministry of Health also found that the country's maternal mortality rate was as high as 182 deaths per 100,000 live births (Shiffman and Garces del Valle 2006). The four major causes of maternal mortality are severe bleeding, infections mostly soon after delivery, hypertensive disorders in pregnancy, and obstructed labor (WHO et al 2007).…”
mentioning
confidence: 98%
“…Since the 1980s Honduras has focused on addressing maternal mortality through prioritization of institutional deliveries as a key means to reduce mortality due to emergency obstetric complications. 40,41 Using the "three delays" framework 41 that was already familiar to participants, we created an initial "backbone" model to elicit information about how the current system was structured. 42 As a result of the various interactions that took place during the following year, participants became deeply engaged in developing increasingly sophisticated models, starting with prototype models and ending with a computer simulation model that is currently under calibration.…”
Section: Sm2015 Honduras Maternal Mortality Modelingmentioning
confidence: 99%
“…10,11 This trend was seen in many more countries such as Mongolia, Egypt and Honduras, among others. [12][13][14] The remarkable declines in maternal mortality achieved by these countries could encourage prioritization of reproductive health generally, and maternal health particularly, elsewhere. Such declines demonstrate that governments can successfully prioritize and establish an on-going commitment to improvements in reproductive health and implement cost-effective, nationally appropriate solutions by following through on their political and financial commitments.…”
Section: Introductionmentioning
confidence: 99%